Natural Geography, Socioeconomic Inequalities, Institutions, and How They Affect Global Homicide Rates - Evangelos Rasvanis (Kriminologie - Das Online-Journal)
Homicide, which represents the most extreme form of violence, significantly devalues human life. This paper examines the impact of natural geography − a factor often underestimated − alongside socioeconomic disparities and institutional performance on global violent crime rates, with a specific focus on homicide. By analyzing data from 180 countries for the years 2002−2021 and applying Generalized Least Squares (GLS) regression models, it finds a significant correlation between geographic conditions and homicide rates. Specifically, it highlights that landlocked countries with higher mean temperatures report lower homicide rates compared to cooler, coastal countries. In addition, the findings reveal that countries with higher economic status, better education and well-functioning institutions tend to exhibit lower homicide rates.